2020
DOI: 10.1002/jso.26129
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐negative apocrine carcinoma: A rare pathologic subtype with a better prognosis than other triple‐negative breast cancers

Abstract: Background and Methods: Apocrine adenocarcinoma is a rare subtype of breast cancer. We sought to compare the characteristics and survival of patients diagnosed with triple-negative apocrine adenocarcinoma to those of patients diagnosed with triple-negative invasive ductal carcinoma. Utilizing data from the National Cancer Database between 2004 and 2013, 70 524 eligible female patients with triplenegative breast cancer were identified including 566 patients with apocrine adenocarcinomas and 69 958 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Our results are in line with a recently published SEER cohort of triple-negative APO carcinomas, which also revealed that these cancers had a better prognosis than TNBC NST [23]. Several other independent studies con rmed a more favorable outcome for triple-negative APO patients [1,17]. In contrast, the studies of Dellapasqua et al [4] and Bonnefoi et al [2] reported a poor outcome of molecular apocrine tumors/pure apocrine carcinomas (as de ned by gene expression analysis and/or immunohistochemistry) from the cohorts of the European Institute of Oncology and the EORTC 10994/BIG 1-00 phase III study, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in line with a recently published SEER cohort of triple-negative APO carcinomas, which also revealed that these cancers had a better prognosis than TNBC NST [23]. Several other independent studies con rmed a more favorable outcome for triple-negative APO patients [1,17]. In contrast, the studies of Dellapasqua et al [4] and Bonnefoi et al [2] reported a poor outcome of molecular apocrine tumors/pure apocrine carcinomas (as de ned by gene expression analysis and/or immunohistochemistry) from the cohorts of the European Institute of Oncology and the EORTC 10994/BIG 1-00 phase III study, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In a large cohort study by Arciero et al, triple-negative apocrine carcinomas TNACs had a significantly better overall survival compared to triple-negative invasive ductal carcinomas TNBCs. Also, their study demonstrated that most TNAC cases were associated with older age, lower T stage, and tumor grade [ 4 ]. Similar results were demonstrated by Wu et al in a large SEER-based study, and in a small limited case–control study by Meattini et al Studies referred this difference to the overexpression of AR and GCDFP-15 which might be associated with a decreased tumor proliferation and subsequently, a better prognosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human epidermal growth factor receptor-2 (HER2/neu) overexpression is present in approximately 50% of apocrine carcinoma cases [ 2 ], whereas HER2-negative apocrine carcinomas are classified as triple-negative apocrine carcinomas (TNACs) which are extremely rare neoplasms constituting less than 1% of all triple-negative breast cancers (TNBCs) [ 3 ]. Although TNBCs have a poor prognosis due to the negative expression of hormone receptors and the inability to apply targeted therapy, triple-negative apocrine carcinomas were found to have a better prognosis and overall survival, which highlights the importance of diagnosing and distinguishing this rare subtype [ 4 ]. Herein, we present the first case report from Syria of a 45-year-old female who was diagnosed with a triple-negative apocrine carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of both SEER database and National Cancer Database (NCD) showed that TNAC has a better prognosis than TNBC [13,14]. Study comparing TNAC that did not receive adjuvant chemotherapy with matched triple negative invasive ductal carcinoma that received adjuvant chemotherapy showed that the two groups share similar prognosis which indicate a potential de-escalation in the management of TNAC [15].…”
Section: Introductionmentioning
confidence: 99%